Cardiac safety of bedaquiline: a systematic and critical analysis of the evidence. Issue 5 (16th November 2017) - Pontali, Emanuele; Sotgiu, Giovanni; Tiberi, Simon; D'Ambrosio, Lia; Centis, Rosella; Migliori, Giovanni B.
The treatment of multidrug-resistant (MDR) or extensively drug-resistant (XDR) tuberculosis (TB) remains a challenge for clinicians for several reasons, including the large number of drugs required, the cost, the tolerability of single drugs and their combinations, and the effectiveness and long treatment duration [1–6]. Therefore, fresh attention has recently been paid to new and repurposed anti-TB drugs [4, 5, 7–18]. Bedaquiline is well tolerated: evidence indicates a minority of patients discontinue use due to QT extension http://ow.ly/9NRT30fNv4y